A critical discussion of the twelve-tonal idiom of Anton Webern and criticism of its assessmant by some natable theorists - Everson, Cromwell (College of Music, 2024)
Webern took over from Schoenberg, and others, and elevated the art of music to an auditory mathernatics. "It is given only to powerful spirits to travel this razor edge. Lesser ones 1 ack the requisite inner certainty. Indeed Webern never pandered to popular taste. iii Every tone he wrote was dictated to by musical necessity ·and logic. No other composer has shown such iron consistency in the development of his art as Webern has. In him we find an evolutionary growth which consistently advanced the frontiers of music and presented the world with a series of masterpieces which,regrettably,are too seldom performed. Yet during his life Webern was scandalously neglected and misunderstood. It pains one to think that the Genius who created the Orchestral Variations uttered these heart-rending words: "Now, my dear chap, say your piece and exert your influence, I beg of you. If only some notice at all could be taken of my work!" It 2 But History plays amazing quirks% Within ten years or so after these words were written Webern became the dominating influence in twentieth century music. His ascent. was so glittering that Posterity named periods in honour of him, that world-famous composers reconstructed their thinking .to write in the Webernite manner. There are few who have attained such a manifestation of power to determine an artistic direction by sheer influence or reaction. Thus we have approached this study of Webern with awe a~d the further we have progressed,the greater has our expression of admiration and humility become.